2002
DOI: 10.2169/internalmedicine.41.972
|View full text |Cite
|
Sign up to set email alerts
|

Primary Amenorrhea Accompanied by Adrenal Adenoma: Start of Menarche Soon after Tumor Resection.

Abstract: Wereport a patient with primary amenorrhea accompanied by adrenal adenoma. A 21-year-old womanwas admitted to our hospital because of primary amenorrhea and hyperprogesteronemia without virilization. Venous sampling showedprogesterone overproduction at the left adrenal gland. Computedtomography revealed a 7 cm mass in left adrenal gland. Serum pregnenorone, 17-hydroxypregnenorone, dehydroepiandrosterone, 17-hydroxyprogesterone, deoxycorticosterone, and 1 1-deoxycortisol were elevated. The diagnosis of steroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In human medicine, adrenal and ovarian venous sampling has been described to differentiate adrenal from ovarian production of progesterone. 13 In women, hyperprogesteronemia usually causes amenorrhea [13][14][15][16][17] ; the dog in Case 1 also had delayed oestrus (13 months, when its owners reported that it previously had regular oestrus every 6 months). The effect of progesterone on the mood and behaviour is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In human medicine, adrenal and ovarian venous sampling has been described to differentiate adrenal from ovarian production of progesterone. 13 In women, hyperprogesteronemia usually causes amenorrhea [13][14][15][16][17] ; the dog in Case 1 also had delayed oestrus (13 months, when its owners reported that it previously had regular oestrus every 6 months). The effect of progesterone on the mood and behaviour is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…There are only few reports of progesterone-secreting adrenocortical tumours in humans, with other intermediate steroids usually being also increased in these cases. [13][14][15][16][17] Clinical signs usually include menstrual disorders with amenorrhea or oligomenorrhea in women. There is no report of this tumour in a human male patient.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone-producing adrenal tumours are extremely rare in humans, with four cases reported in women with secondary amenorrhoea or oligomenorrhoea. 34 37 …”
Section: Discussionmentioning
confidence: 99%
“…Progesterone-producing adrenal tumours are extremely rare in humans, with four cases reported in women with secondary amenorrhoea or oligomenorrhoea. [34][35][36][37] Mammary enlargement in male cats is rare and can be caused by neoplasia or fibroadenomatous hyperplasia (MFH). 38 MFH is a benign proliferation of ductal epithelium and mammary stroma, usually seen in young female cats.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, however, the total number of the report of adrenal tumor producing mineralocorticoid intermediates was not so large even now. Progesterone producing adrenal tumors are even rarer [5,6]. Only two cases with progesterone producing adrenal tumors have been reported, and both presented with amenorrhea.…”
Section: Introductionmentioning
confidence: 99%